2017
DOI: 10.18632/oncotarget.14625
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA growth arrest specific transcript 5 acts as a tumour suppressor in colorectal cancer by inhibiting interleukin-10 and vascular endothelial growth factor expression

Abstract: Long non-coding RNAs (lncRNAs) are highly involved in diverse biological processes of human malignancies. The expression profile and underlying mechanism of lncRNA growth arrest specific transcript 5 (GAS5) in colorectal cancer (CRC) is poorly understood. In this study, we found that GAS5 was commonly downregulated in CRC tissues, serum of CRC patients and CRC cell lines. Knockdown of GAS5 promoted CRC cell proliferation and colony formation, whereas overexpression of GAS5 produced the opposite result. We furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 46 publications
(44 reference statements)
1
42
0
Order By: Relevance
“…LncRNAs expressed in tumor cells may affect not only the tumor cells but also tumor-directed immune responses. For example, the tumor-suppressive growth arrest-specific transcript 5 (GAS5) lncRNA was reported to be associated with the expression of VEGF-A and IL-10 in the tumor cells (49). VEGF-A is a well-known proangiogenic molecule produced by the tumor cells.…”
Section: Pro-tumoral Cytokinesmentioning
confidence: 99%
“…LncRNAs expressed in tumor cells may affect not only the tumor cells but also tumor-directed immune responses. For example, the tumor-suppressive growth arrest-specific transcript 5 (GAS5) lncRNA was reported to be associated with the expression of VEGF-A and IL-10 in the tumor cells (49). VEGF-A is a well-known proangiogenic molecule produced by the tumor cells.…”
Section: Pro-tumoral Cytokinesmentioning
confidence: 99%
“…(growth arrest-specific 5) lncRNA acts as a tumor suppressor with various proposed mechanisms of action, including, cell cycle control Mazar et al 2016;Luo et al 2017), proliferation (Kino et al 2010;Li et al 2017b) and regulation of epithelial to mesenchymal transition (EMT) program (Zhuang et al 2015). Considering the multi-faceted mechanisms by which GAS5 functions as a tumor suppressor, it is plausible that its expression may be predictive of response to multiple drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that the expression and secretion of IL‐10 and VEGF‐A were increased by knockdown of GAS5 , via NF‐κB and ERK1/2 pathways. Furthermore, neutralization of IL‐10 and VEGF‐A reduces tumor proliferation caused by GAS5 knockdown …”
Section: Lncrnas In Hallmarks Of Cancermentioning
confidence: 99%
“…Furthermore, neutralization of IL-10 and VEGF-A reduces tumor proliferation caused by GAS5 knockdown. 148…”
Section: Inflammation and Evasion Of Immune Destructionmentioning
confidence: 99%